Fluxo de gases de efeito estufa em sistemas de preparo do solo e rotação de culturas no planalto do Rio Grande do Sul - Pes, Luciano Zucuni (2009)
The main greenhouse gases (GHG) are the nitrous oxide (N2O), methane (CH4) and carbon dioxide (CO2), whose atmosphere concentrations increased in an unprecedented rate since the Industrial Revolution. This work aim evaluates the GEE emissions of spring/summer season in different soil management systems located in the Planalto region of Rio Grande do Sul State. This work was carried out in a long term experiment (22 years), located at FUNDACEP research center under a Rhodic Hapludox soil. This research was split in two studies: the first had the objective of evaluated the CO2 short-term emissions (21 days) during the tillage systems activities and cropping establishment under conventional tillage (CT) and no-tillage (NT) using a dynamic camera (Flux Chamber 6400-09, Licor). The second study aim evaluate the three main GEE, during the period from October/2007 to January/2008 period, totalizing 101 days, including the activities of soil tillage, establishment and part of the corn and soybean growing stage, under CT, NT and NT with wheat residues (NT-w). In this study in the static camera method, 11 air samples were collected using syringe at 0, 15, 30 and 45 minutes after the closing of the camera. The concentration of GEE were analyzed by gaseous chromatography. In the first study, CT presented accumulated CO2 emission 42% higher than NT, and the main source of CO2 in CT was associated to the residue decomposition and the release of soil CO2, while the gas efflux in NT was associated to the decomposition of soil organic matter. In the second study, all of the tillage systems were N2O source, being higher in NT. For CH4, all of the tillage systems, in the average of the period were a sink of this gas, being higher in NT-w. In relation to CO2, all of the systems were a source of this gas, being higher in CT and it was verified a seasonal effect in CO2 emissions, being higher in spring/summer seasons. The mitigation of the GEE emissions would be achieved by applying conservation tillage systems, with low soil disturbance, and rationalization in the mineral N fertilization.